Characterization of an adulticidal and larvicidal interfering RNA pesticide that targets a conserved sequence in mosquito G protein-coupled dopamine 1 receptor genes. (May 2020) - Hapairai, Limb K.; Mysore, Keshava; Sun, Longhua; Li, Ping; Wang, Chien-Wei; Scheel, Nicholas D.; Lesnik, Alexandra; Scheel, Max P.; Igiede, Jessica; Wei, Na; Severson, David W.; Duman-Scheel, Molly
Abstract: G protein-coupled receptors (GPCRs), key regulators of a variety of critical biological processes, are attractive targets for insecticide development. Given the importance of these receptors in many organisms, including humans, it is critical that novel pesticides directed against GPCRs are designed to be species-specific. Here, we present characterization of an interfering RNA pesticide (IRP) targeting the mosquito GPCR-encoding dopamine 1 receptor (dop1) genes. A small interfering RNA corresponding to dop1 was identified in a screen for IRPs that kill Aedes aegypti during both the adult and larval stages. The 25 bp sequence targeted by this IRP is conserved in the dop1 genes of multiple mosquito species, but not in non-target organisms, indicating that it could function as a biorational mosquito insecticide. Aedes aegypti adults treated through microinjection or attractive toxic sugar bait delivery of small interfering RNA corresponding to the target site exhibited severe neural and behavioral defects and high levels of adult mortality. Likewise, A. aegypti larval consumption of dried inactivated yeast tablets prepared from a Saccharomyces cerevisiae strain engineered to express short hairpin RNA corresponding to the dop1 target site resulted in severe neural defects and larval mortality. Aedes albopictus and Anopheles gambiae adult and larval mortality was also observed following treatment with dop1 IRPs, which were not toxic to non-target arthropods. The results of this investigation indicate that dop1 IRPs can be used for species-specific targeting of dop1 GPCRs and may represent a new biorational strategy for control of both adult and larval mosquitoes. Graphical abstract: Image 1 Highlights: RNAi pesticides targeting mosquito dopamine 1 receptor (dop1) genes kill adults and larvae. RNAi pesticides targeting dop1 can be delivered to adults as attractive toxic sugar baits. Yeast that express RNAi pesticides targeting dop1 kill mosquito larvae upon consumption. Interfering RNA pesticides can be used for species-specific targeting of mosquito dop1 GPCRs. RNAi-based pesticides targeting dop1 may represent a new biorational mosquito control strategy.